Workplace Requirements in New Normal Era due to COVID-19 Pandemic: Design Criteria and Health Environment Perspectives - Undayani Cita Sari; Rani Tiyas Budiyanti (Journal of Public Health for Tropical and Coastal Region, 2020)
New normal era is being done in many countries after COVID-19 pandemic. This era allows people back to office with certain condition. Many requirements must be fulfilled in workplace before starts new normal era. This study aims to identification workplace requirements in new normal era. Evaluation of this study obtained from design engineering criteria and health environment perspective which used literature review method. Based on the analysis, it shows that there are many requirements that must be fulfilled to create safety zone in workplace in new normal era such as workspace layout, ventilation, lighting, establishment of equipment, and thermal comfort. Design of workplace which is ergonomic and health environment also be developed in this research. However, employee still keep applying health protocol in office.